The Effect Of Liquid Organic Fertilizer Of Robusta Coffee On The Productivity Of Red Cry Chili (Capsicum annum L.) - Yuli Cahya Ningsih; Ervina Titi Jayanti; M. Harja Efendi (PENBIOS: JURNAL PENDIDIKAN BIOLOGI DAN SAINS, 2020)
This study aims to determine the effect of liquid organic fertilizerfrom Robust coffee peels on the productivity of curly red chilies(Capsicum annum L). This type of research is quantitative, theresearch approach used is experimental by using a completelyrandomized design RAL consisting of 7 treatments of 5 replicationsso that there are 35 experimental units and are placed randomly,namely 0% fertilizer (P0), 10% fertilizer (P1), fertilizer. 20% (P2),30% fertilizer (P3), 40% fertilizer (P4), 50% fertilizer (P5), 60%fertilizer (P6). The data analysis technique used One-way ANOVAwith a significance level of 5% and the LSD advanced test. ANOVAtest results show that the comparison of the effect of liquid organicfertilizer on robust coffee peels has an effect on vegetative growthand generative growth in curly red chilies (Capasicum annum L.).Fertilizer treatment with a concentration of 50% (P5) had the mostsignificant effect on the number of flowers, number of fruits, wetweight and dry weight of curly red chilies. On the growth of thenumber of leaves, the concentration of 30% (P3) also gave the highesteffect and yield although not significant. The 50% concentration (P5)was the optimal concentration for the growth of plant height andlength of curly red chili plants.